African and Islamic: Lessing’s theory of literature in “The Small Personal Voice” - Hasan, Md. Mahmudul (2019)
In “The Small Personal Voice” (1957), Doris Lessing celebrates novels that are based on nineteenth-century realism and writerly committedness and laments its absence in literary production. She adheres to a theory of literature that emanates from an understanding of good and evil and has an instructive function. In this respect, she admires nineteenth-century realist novelists and commends their efforts to document the social abuses of the period and thus to right the wrongs committed by exploitative elements in society. Despite the debate whether or not later in her works Lessing held true to the position detailed so powerfully in “The Small Personal Voice”, the essay is often considered her manifesto and synonymous with her name. Paraphrasing Wordsworth that “the novelist talks, as an individual to individuals, in a small personal voice” (Lessing 25), and given the urgency of morally and socially edifying literary texts, she vaticinates that readers will “feel again a need for the small personal voice.” Based on this background, my paper will elaborate on Lessing’s theory of literature as a counter to the overarching philosophy of the “art for art’s sake” movement and will establish resonances of her theory with those of African and Islamic views of literature.